Família(s), escolarização e trajetória de jovens : da educação básica ao ensino superior público em Sergipe - Souza, Laís Santana Santos (2014)
This study aims to investigate the role that families play in the process of education of the children, yesterday, students of basic education, today, college students. The subjects of the research were University students at the Federal University of Sergipe, linked to different courses and academic centres, as well as their families. We seek to identify the process of Constitution (or not) of strategies relatives of schooling in their school routes, whereas the trajectory described between basic education and tertiary education. For that, we are about the literature that discusses the issues related to the relationship between family and school, watching the debate about practices and strategies of family education of the children as well as the transformations observed in higher education in Brazil. The adopted methodology is characterized by their qualitative nature, focused on the combination of different instruments of collection and production of data: questionnaires and learn swing among the college students and interviews with the families. Among the results, obtained in the survey, we highlight the following: the population of University students of UFS is, increasingly, young mothers and older brothers were cited by investigated as the main subject that perform practices, tactics and/or educational strategies vis-à-vis the schooling of these families are so big importance on higher education of the children and in basic education. It is up to us, therefore, the alert that families should not be seen, evenly, nor how powerful institutions, but have it your place of performance which is singular. Despite the limitations of this study, we intend to introduce it your contribution in the set of productions that has launched its look at the complex relationship between families and education.